НАСЛІДУВАННЯ В ПРОЦЕСІ НАВЧАННЯ ЧИТАННЮ НОТ З АРКУША (Педагогіка вищої та середньої школи, 2002)
This article investigates the role and importance of imitation in the process of rea-ding musical notation as a specific psychological process with definite mechanisms and stages of its development. The results of the author's observation, as well as the teacher's role in the process of reading musical notation, are reported.